Cholinergic Dysfunction Involvement in Chronic Cerebral Hypoperfusion-Induced Impairment of Medial Septum–dCA1 Neurocircuit in Rats - Xu, Yi; Zhang, Shuai; Sun, Qiang; Wang, Xu-Qiao; Chai, Ya-Ni; Mishra, Chandan; Chandra, Shah Ram; Ai, Jing (Frontiers in Cellular Neuroscience, 2020)
Chronic cerebral hypoperfusion (CCH) is considered a preclinical condition of mild cognitive impairment and thought to precede dementia. However, as the principal cholinergic source of hippocampus, whether the septo-hippocampal neurocircuit was impaired after CCH is still unknow. In this study, we established the CCH rat model by bilateral common carotid artery occlusion (2VO). Under anesthesia, the medial septum (MS) of rats was stimulated to evoke the field excitatory post-synaptic potential (fEPSP) in the pyramidal cell layer of dCA1. Consequently, we observed decreased amplitude of field excitatory post-synaptic potential and increased paired-pulse ratio (PPR) after 8-week CCH. After tail-pinch, we also found decreased peak frequency and shortened duration of hippocampal theta rhythm in 2VO rats, indicating the dysfunction of septo-hippocampal neurocircuit. Besides, by intracerebroventricularly injecting GABAergic inhibitor (bicuculine) and cholinergic inhibitors (scopolamine, and mecamylamine), we found CCH impaired both of the pre-synaptic cholinergic release and the post-synaptic nAchR function in MS-dCA1 circuits. These results gave an insight into the role of CCH in the impairment of cholinergic MS-dCA1 neurocircuits. These findings may provide a new idea about the CCH induced neurodegenerative changes.